Death, Taxes and Advance Directives - Wood, N.M.; D‘Amore, J.D.; Jones, S.L.; Sittig, D.F.; Ness, R.B. (Applied Clinical Informatics, 2014)
Suboptimal care at the end-of-life can be due to lack of access or knowledge of patient wishes. Ambiguity is often the result of non-standardized formats. Borrowing digital technology from other industries and using existing health information infrastructure can greatly improve the completion, storage, and distribution of advance directives. We believe several simple, low-cost adaptations to regional and federal programs can raise the standard of end-of-life care.Citation: Wood NM, D’Amore JD, Jones SL, Sittig DF, Ness RB. Death, taxes and advance directives. Appl Clin Inf 2014; 5: 589–593 http://dx.doi.org/10.4338/ACI-2013-12-IE-0099
Keywords: Health information exchange; end of life; advance directive